The January seasonality and the performance of country-level value and momentum strategies - Zaremba, Adam (Copernican Journal of Finance & Accounting, 2015)
The study examines the turn-of-the-year effect in the country-level value and momentum strategies. We re-examine eight distinct value and momentum strategies within 78 markets in the 1995‑2015 period and we test their performance for the seasonal patterns. We find that during the last 20 years the value strategies performed particularly well in January and poor in December. On the contrary, the momentum strategies had high returns in December and low in January. These observations are consistent with the explanations of the January seasonality related to the tax loss selling and window dressing effects.